(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the role and importance of social and humanities disciplines in shaping tolerance, interethnic harmony, and humanistic values in the minds of the younger generation in New Uzbekistan. The author explores ways to elevate the worldview, spiritual level, and communication culture of young people through disciplines such as philosophy, history, sociology, psychology, political science, and cultural studies. The article describes methods of promoting tolerance in the educational process, modern approaches to moral and spiritual education, and the scientific-theoretical foundations for establishing tolerance in the consciousness of youth. The research results show that strengthening the role of social and humanities disciplines in the education system serves to reinforce an environment of harmony and mutual respect among young people.